Driving Factors on Indonesian EFL Learners’ Willingness to Communicate (WTC) Using English: State of the Arts and Ways Forward - Ustadzah; M.Farkhi Faishol Hakim (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
EFL students' communication ability is still far behind expectations due to their poor readiness to talk. It is unrealistic to expect students who are reluctant to speak in English to improve their communication abilities. The current study is undertaken to analyze the variables effect Indonesian EFL learners’ WTC in English class at secondary school and the teaching techniques may be utilized to encourage Indonesian EFL learners’ WTC in English class at secondary school. The current study offers a thorough literature evaluation of WTC research within the specific domain of EFL learners’ of secondary school in Indonesia. The Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guidelines were used in this review research to examine publications from Google Scholar. The papers included are 6 recognized journal articles identified in google scholar throughout the timeframe 2020 - 2024. The results shown that a number of variables, divided into situational and individual aspects, influence EFL learners' WTC. However, the tactics that EFL teachers might employ are: arranging the students’ chairs in a U shape, practicing Out-of-class English communications, using technology in language learning, and following conversation club. It is anticipated that teachers would use a variety of strategies to encourage more student participation throughout the class after identifying the contributing elements.